IMPROVEMENT OF LEGISLATION ON COMBATING ORGANISED CRIME AS A COMPONENT OF STATE SECURITY - Tkachenko, Oleksandr; Maltsev, Vitalii (Honor and Law, 2023)
Organised crime, with the development of technologies and means of communication, is acquiring new forms and new content, which negatively affects the political, economic and other spheres of the country’s activity and the State security in general. The authors analyse the current legislation and doctrinal regulations in the area of combating organised crime, and on this basis draw attention to the lack of systemic counteraction to organised crime. The authors offer their vision of improving certain measures to combat organised crime in Ukraine. The doctrinal regulatory documents are reviewed. Based on the opinions of scholars, practitioners and experts on their effectiveness, the author suggests areas for their improvement. Attention is drawn to the importance of defining the system of actors involved in combating organised crime, delineating tasks and vesting them with appropriate powers based on the purpose of their activities. The results of the activities of the National Police units in the fight against organised crime in 2023 are presented. The author outlines the issues related to the participation of the National Police in the fight against organised crime in the system of actors in the fight against organised crime. Proposals are made to improve the legislation on combating organised crime, the systematic nature of which should be based on the introduction of new and improvement of existing provisions of criminal, administrative, economic, financial, tax legislation, and the practice of their application, and bringing them into line with each other in order to avoid discrepancies and contradictions between legal acts regulating the same or related legal relations, as well as the competence of the actors involved in the fight against organised crime.